Social network restructuring after a node removal. (1st January 2013) - Missaoui, Rokia; Negre, Elsa; Anggraini, Dyah; Vaillancourt, Jean
Central nodes (i.e., prominent actors) in a social network are those that are linked to other nodes in an extensive or critical manner. Therefore, their removal may lead to points of failure. The objective of the present work is to exploit network topology to devise an approach towards: 1 finding a substitute to a deleted node if the latter is a central one 2 adding appropriate links to maintain the network connected. The approach exploits the role played by nodes to predict the new structure of a social network once one entity disappears. The role of a node in the network is expressed in terms of its centrality in the network. Three important roles are considered: the leader, the mediator and the witness . An entity acts as a leader, a mediator or a witness if it has a high degree centrality, betweenness centrality and closeness centrality, respectively.